Sequence diversity in the A domain of Staphylococcus aureus fibronectin-binding protein A - Loughman, Anthony (BioMed Central, 2008)
BACKGROUND: Fibronectin-binding protein A (FnBPA) mediates adhesion of Staphylococcus aureus to fibronectin, fibrinogen and elastin. We previously reported that S. aureus strain P1 encodes an FnBPA protein where the fibrinogen/elastin-binding domain (A domain) is substantially divergent in amino acid sequence from the archetypal FnBPA of S. aureus NCTC8325, and that these variations created differences in antigenicity. In this study strains from multilocus sequence types (MLST) that spanned the genetic diversity of S.aureus were examined to determine the extent of FnBPA A domain variation within the S. aureus population and its effect on ligand binding and immuno-crossreactivity. RESULTS: Seven different isotype forms (I – VII) of the FnBPA A domain were identified which were between 66 to 76% identical in amino acid sequence in any pair-wise alignment. The fnbA allelic variants in strains of different multilocus sequence type were identified by DNA hybridization using probes specific for sequences encoding the highly divergent N3 sub-domain of different isotypes. Several isotypes were not restricted to specific clones or clonal complexes but were more widely distributed. It is highly likely that certain fnbA genes have been transferred horizontally. Residues lining the putative ligand-binding trench were conserved, which is consistent with the ability of each A domain isotype to bind immobilized fibrinogen and elastin by the dock-latch-lock mechanism. Variant amino acid residues were mapped on a three-dimensional model of the FnBPA A domain and were predicted to be surface-exposed. Polyclonal antibodies raised against the recombinant isotype I A domain bound that protein with a 4 – 7 fold higher apparent affinity compared to the A domains of isotypes II – VII, while some monoclonal antibodies generated against the isotype I A domain showed reduced or no binding to the other isotypes. CONCLUSION: The FnBPA A domain occurs in at least 7 different isotypes which differ antigenically and exhibit limited immuno-crossreactivity, yet retain their ligand-binding functions. Antigenic variation of the FnBPA A domain may aid S. aureus to evade the host's immune responses. These findings have implications for the development of vaccines or immunotherapeutics that target FnBPA.